Methods for Blind Estimation of the Variance of Mixed Noise and Their Performance Analysis - Abramov, Sergey; Zabrodina, Victoria; Lukin, Vladimir; Vozel, Benoit; Chehdi, Kacem; Astola, Jaakko (IntechOpen, 2011)
None